THE ROLE OF APPLYING THE REQUIREMENTS OF THE ENVIRONMENTAL MANAGEMENT SYSTEM (ISO14001) IN INCREASING THE MARKET SHARE FROM THE POINT OF VIEW OF THE EMPLOYEES OF MOHAMMED AL-ZAILAI & PARTNERS COMPANY - Raed Abdalgabbar Khudhur (Scholar Express Journal, 2022)
This study aimed to highlight the role of applying the requirements of the environmental management system (ISO14001) in increasing the market share from the viewpoint of the employees of Mohammed Al-Zailai& Partners Company. To achieve the objectives of the study, a questionnaire was designed and distributed to the research sample (14) workers of Muhammad Al-Zaylai and Partners Company). Moreover, 14 questionnaires were distributed, of which 12 were retrieved, with a percentage of (85.7%), valid for analysis. The descriptive analytical method was used to describe the research variables . The research presented a number of results, the most important of which are: • There is a significant role for the application of the requirements of the environmental management system (ISO14001) in increasing the market share from the point of view of the employees of Mohammed Al-Zailai & Partners Co. The study concluded with a number of recommendations, the most important of which are: • The necessity of spreading environmental culture and emphasizing the importance of the environmental management system in protecting the environment. • The institution must rely on a clear and specific strategy for the environmental management system in order to achieve the optimal investment of resources, in a way that helps reduce waste and costs and creates an appropriate industrial environment that takes into account environmental requirements. • The institution should work to increase interest in the environment by activating communication tools with the authorities concerned with environmental affairs in order to avoid environmental risks. • Activating the role of employees in the institution by involving them in the application of specifications and preparing plans for improving environmental conditions and gaining their loyalty.
Keywords: Environmental policy; environmental planning; implementation and operation; market share